Answer:
x = -7
Step-by-step explanation:
5(x-2)=3x+4(x+1)
First, multiply the 5 with the x and the 5 with the -2. You are using the distributive property.
5x -10 = 3x + 4 (x+1)
Then multiply the 4 with the x and the 4 with the 1 on the other side. Again, you are using the distributive property.
5x-10=3x+4x+4
Next, combine like terms. So you're going to combine the 3x and the 4x on the right side.
5x-10=7x+4
Then, subtract 5x from both sides. Also, subtract the 4 from both sides. You do this in order to get all of the x's on one side of the equation.
-14 = 2x
Finally, divide 2 from both sides. You do this because right now, the equation says 2 times x, and you need to get the x alone.
-7 = x
You are finished